Ruthenocenyl ruthenium bimetallic complexes: Electrospray mass spectrometric study of [RuX(η5-C5H5)(η2-dppr)] n+ (dppr=1,1′-bis(diphenylphosphino)ruthenocene) (X=Cl, n=0; X=CO, CH3CN, C=CHPh, n=1) and the X-ray crystal and molecular structure of [Ru(η5-C5H5)(CO)(η 2-dppr)]PF6 - Po Yeo, S. (2014)
Journal of Organometallic Chemistry